تحسين الصلابة ومقاومة ألاحتكاك للفولاذ الصلبAISI H12 باستخدام الطلاء الصناعى (كربيد التنغستن) (Comprehensive Journal of Science, 2025)
In this research, the effect and effectiveness of industrial coating, tungsten carbide coating on the tribological performance of AISI H12 tool steel was studied through wear test. We performed an analysis of the tungsten carbide coating on the erosion performance of H12 steel using optical techniques such as scanning electron microscopy (SEM), three-dimensional topographic images, and a coefficient of friction experiment. According to the results obtained from the erosion tests, tungsten carbide-coated steel reduced the coefficient of friction by 23.2% compared to uncoated steel. The aim of this study is to increase the wear resistance of H12 hot work steel, by using tungsten carbide coating.
Keywords: Electron Microscope (SEM), Energy Dispersive X-ray analysis (EDX), American Iron and Steel Institute (AISI), Coefficient Of Friction , tungsten carbide coating, (WC) , H12 tool steel, High Velocity Oxygen Fuel (HVOF), hardness